2023
DOI: 10.1111/1755-6724.15034
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, Geochemistry and Petrogenesis of the Bangbule Quartz Porphyry: Implications for Metallogenesis

Abstract: The Bangbule skarn lead‐zinc (Pb‐Zn) deposit (>1 Mt Zn + Pb) is located in the western Nyainqentanglha polymetallic metallogenetic belt, central Tibet. Lenticular orebodies are all hosted in skarn and developed in the contact zone between the quartz porphyry and carbonate strata of the mid Paleozoic Middle to Upper Chaguoluoma Formation as well as in carbonate and sandstone beds of the Upper Paleozoic Laga Formation. As a newly discovered skarn deposit, the geological background and metallogenesis of this depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The boundary between the northern and central terranes is the Shiquanhe Namucuo ophiolite mélange belt, while the Luobadui Mila Mountain fault delineates the boundary between the central and southern terranes (Zhu et al, 2011). The Gangdese volcanicmagmatic arc, part of the Himalayan Tethyan metallogenic domain, is notable for its frequent tectonic activity, widespread igneous rocks (Dong et al, 2023;He et al, 2023), and extensive hydrothermal alterations, leading to the genesis of multiple porphyry-skarn-type copper deposits, with Jiama being a prominent example.…”
Section: Geological Settingmentioning
confidence: 99%
“…The boundary between the northern and central terranes is the Shiquanhe Namucuo ophiolite mélange belt, while the Luobadui Mila Mountain fault delineates the boundary between the central and southern terranes (Zhu et al, 2011). The Gangdese volcanicmagmatic arc, part of the Himalayan Tethyan metallogenic domain, is notable for its frequent tectonic activity, widespread igneous rocks (Dong et al, 2023;He et al, 2023), and extensive hydrothermal alterations, leading to the genesis of multiple porphyry-skarn-type copper deposits, with Jiama being a prominent example.…”
Section: Geological Settingmentioning
confidence: 99%
“…According to studies, the main factor causing mineralization is the high oxygen fugacity of the magma (Sillitoe, 2010;Zhang et al, 2022;He et al, 2023). Numerous studies have shown that the ability of magma to S is proportional to the oxygen fugacity, and the content of S in magma determines whether it is mineralized (Parat et al, 2008;Botcharnikov et al, 2011;Hu et al, 2023).…”
Section: Indication To the Evolution Of The Shallow Magma Chambermentioning
confidence: 99%